An Opportunity to Fill a Gap for Newborn Screening of Neurodevelopmental Disorders - Wendy K. Chung; Stephen M. Kanne; Zhanzhi Hu (MDPI AG, 2024)
Screening newborns using genome sequencing is being explored due to its potential to expand the list of conditions that can be screened. Previously, we proposed the need for large-scale pilot studies to assess the feasibility of screening highly penetrant genetic neurodevelopmental disorders. Here, we discuss the initial experience from the GUARDIAN study and the systemic gaps in clinical services that were identified in the early stages of the pilot study.